The Position of Non-Member States in the International Criminal Court Regarding Its Decisions to Hold War Criminals Accountable: Putin and Netanyahu as a Model: international and political journal - Sekeb, Noor Ali Lecturer. Dr (The International and Political Journal, 2025)
The International Criminal Court (ICC) is one of the most prominent international judicial institutions aimed at holding perpetrators of international crimes accountable, including genocide, war crimes, and crimes against humanity. Despite its declared objectives of achieving international justice, the ICC's work has sparked widespread controversy among both member and non-member states. This debate is particularly evident in the positions of non-member states toward the Court's decisions, especially those targeting prominent political figures such as Russian President Vladimir Putin and former Israeli Prime Minister Benjamin Netanyahu.This study examines the stance of non-member states on the ICC's decisions aimed at holding war criminals accountable, focusing on the cases of Vladimir Putin and Benjamin Netanyahu.